(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The aim of the study is to clarify the factors that determine the industry-specific nature of the Russian economy in modern conditions. The article discusses the indicators of the technogenic impact of sectors of the economy on the ecosystems of the Russian Federation environment, analyzes its impact on the socio-ecological and economic well-being of citizens, argues organizational and economic measures aimed at greening economic activity.